Providing black soldier fly maggot flour (Hermetia illucens) as a substitute for concentrated feed for the low density lipoprotein (LDL) and high density lipoprotein (HDL) content of broiler chickens - Sisda Indah Millenia Kartika; Sri Hidanah; Adiana Mutamsari Witaningrum; Ratna Damayanti; Widya Paramita Lokapirnasari; Sunaryo Hadi Warsito (Universitas Airlangga, 2024)
This study aims to determine the effect of concentrate substitution with maggot black soldier fly flour in the ration on the percentage of Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL) in broilers. This study used 20 broilers strain Cobb 500 aged five weeks. The P0 group was given a basal diet consisting of 30% concentrate, 60% corn, and 10% rice bran. Groups of P1, P2, P3, and P4 were given basal diet with concentrate substitution of 2, 4, 6, 8% with maggot flour, respectively. Data collection was carried out at the end of the study. Analysis of Variance (ANOVA) showed that the substitution of concentrate with maggot flour from black soldier flies had no significant effect (p>0.05) on the percentage of Low Density Lipoprotein (LDL) and High Density Lipoprotein(HDL)